Systemic Lupus Erythematosus Complicated with Hypertrophic Cardiomyopathy: A Case Report and Literature Review - Huihui Ma; Xin Cao; Jing Zhang; Yongmei Zhou; Rong Luo; Tao He; Jianhong Tao; Xiaoping Li (Case Reports in Cardiology)
A 32-year-old female with systemic lupus erythematosus (SLE) for more than 7 years, and long-term treatment with cyclophosphamide, cyclosporine, methotrexate, and tacrolimus, later found to be combined with hypertrophic cardiomyopathy (HCM) for one year. The patient denied a family history of cardiomyopathy and sudden cardiac death (SCD). Echocardiography suggested that uneven thickening of the left ventricle (LV), mainly in the lower middle segment. Cardiac magnetic resonance (CMR) showed that the walls of the left ventricular (LV) were significantly thickened, as about 21 mm, mainly in the middle and lower segments. Genetic tests showed no known or suspected pathogenic variations were found and no significant enhancement in CMR, so secondary HCM was diagnosed clinically. After symptomatic treatment, the patient was discharged, and long-term follow-up was conducted. The diagnosis of HCM, which combined with SLE or second to usage of tacrolimus, was based on symptoms, echocardiography, and CMR; no endomyocardial biopsies were performed.